1968
DOI: 10.1172/jci105732
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of hemophilia B: detection by means of a specific PTC inhibitor

Abstract: A 1 siI R A C T I lemophilia B can l)e divided into at least two miuitant forms (lifferelit from the n1ild, moderate, and severe categories l)reviously (lescribe(l. Tn about 90% of hemiophilia B patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 5 publications
3
38
0
1
Order By: Relevance
“…On the other hand, most antigen assays of factor IX have been indirect, based upon neutralization of an antibody's inhibition of factor IX clotting activity. Antibodies used have been either human circulating anticoagulants (1) or antisera prepared in rabbits against partially purified factor IX preparations (2). However, tests with either of these preparations have lacked sensitivity, the lack of specificity has been an addiThe Journal of Clinical Investigation Volume 59 May 1977-900-910 900 tional problem with rabbit antisera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, most antigen assays of factor IX have been indirect, based upon neutralization of an antibody's inhibition of factor IX clotting activity. Antibodies used have been either human circulating anticoagulants (1) or antisera prepared in rabbits against partially purified factor IX preparations (2). However, tests with either of these preparations have lacked sensitivity, the lack of specificity has been an addiThe Journal of Clinical Investigation Volume 59 May 1977-900-910 900 tional problem with rabbit antisera.…”
Section: Introductionmentioning
confidence: 99%
“…In groups of patients with hemophilia B, the majority of cases have been associated with either undetectable (1,11,12) Factor IX was isolated from plasma and was used to produce a specific rabbit anti-factor IX antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Elucidation of the nature of the defect in abnormal Factor IX molecules found in some patients with hemophilia B (Christmas disease) may provide insights into function of normal Factor IX in hemostasis and its interaction with other clotting factors. Roberts et al (12), and other investigators (13)(14)(15)(16)(17)(18)(19) have demonstrated that some patients with hemophilia B possess an abnormal Factor IX molecule which has low to undetectable clotting activity, but which is present in relatively normal amounts when measured by immunological techniques (12,(20)(21)(22). Because they contain cross-reacting material (CRM)l to specific homologous and heterologous anti-Factor IX antibodies, these patients have been termed CRM+ (CRM positive variants).…”
mentioning
confidence: 99%
“…Peripheral smears made directly from finger stick were examined for platelet morphology and clumping. Factors VIII, IX, X, and XI1 assays were performed by methods based on PT or PTT (4,10,22,23). The PTA and Fletcher factor deficiencies were excluded by assays based on celite-exhausted plasma (13).…”
Section: Methodsmentioning
confidence: 99%